Pengaruh pemberian pupuk organic cair (POC) batang pisang (Musa Sp.) terhadap tumbuhan dan produktivitas tanaman cabai merah (Capsicum annuum L.) di desa Muka Paya - Antika Rahayu; Hayatul Nurul Fitri (SEMINAR NASIONAL PENINGKATAN MUTU PENDIDIKAN, 2021)
The purpose of this study was to determine the effect of banana stem POC on plants and chili plant productivity to determine the effective concentration of banana stem POC on the growth and productivity of chilies. This research was conducted in one of the house yards in Muka Paya Village, Dusun 4, Hinai District, Langkat Regency, North Sumatra. The tools used were machete tripe, hoe, rake and chopper used to clean the research area, saws, pliers, boards, brushes, paint, buckets, nails and hammers were used to make the research plot planks. The method used was a randomized block design (RBD) consisting of 6 treatments